Excess Liquidity, Moral Hazard, and Credit Risk in Indonesian Commercial Banks - Jeffry Fauzan; Dewi Hanggraeni (Green Publisher Indonesia, 2026)
This research investigates how liquidity creation induces moral hazard behavior and affects credit quality in Indonesian commercial banks. This study examines the effect of liquidity creation, liquidity risk, and central bank policies on credit risk in Indonesian commercial banks, proxied by the non-performing loan (NPL) ratio. Using panel data from 46 banks listed on the Indonesia Stock Exchange over 2015–2024, we apply the Two-Step System Generalized Method of Moments (SYS-GMM) to address endogeneity inherent in dynamic panel models. Results indicate that liquidity creation has a significant positive effect on NPL, consistent with the moral hazard hypothesis. Liquidity risk (LDR) also significantly and positively affects NPL. Reserve requirements (GWM) and BI-Rate do not produce a direct and significant effect on NPL. Return on assets (ROA) significantly and negatively affects NPL. These results suggest that credit risk in Indonesian commercial banking is predominantly influenced by bank-level intermediation behavior rather than by macroeconomic or policy variables. The research concludes that excess liquidity conditions incentivize aggressive credit expansion without proportionate attention to borrower quality, particularly in an oligopolistic market structure with implicit state guarantees.